Self-Assembly of Proteins into Three-Dimensional Structures Using Bio-Conjugation. Issue 1663 (6th May 2014) - Thakur, Garima; Prashanthi, Kovur; Thundat, Thomas
ABSTRACT: Self–assembly of molecular building blocks provides an interesting route to produce well-defined chemical structures. Tailoring the functionalities on the building blocks and controlling the time of self-assembly could control the properties as well as the structure of the resultant patterns. Spontaneous self-assembly of biomolecules can generate bio-interfaces for myriad of potential applications. Here we report self-assembled patterning of human serum albumin (HSA) protein in to ring structures on a polyethylene glycol (PEG) modified gold surface. The structure of the self-assembled protein molecules and kinetics of structure formation entirely revolved around controlling the nucleation of the base layer. The formation of different sizes of ring patterns is attributed to growth conditions of the PEG islands for bio-conjugation. These assemblies might be beneficial in forming structurally ordered architectures of active proteins such as HSA or other globular proteins.